The Influence of Product Quality and KPOP Album Prices on Purchasing Decisions of the KPOP Community Via Shopee Application (Case Study of KPOP Customers in Bandung City) - Moh. Aep Nurjamad; Esti Winidya Gumati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted of the KPOP Bandung community on X (Twitter). The aim of this research is to find out how much influence the product quality and price of KPOP albums have on the purchasing decisions of the KPOP community via the Shopee application, either partially or simultaneously. The research methods used in this research are descriptive methods and associative methods. The sampling technique was by using purposive sampling of 213 populations and 139 respondents obtained from Yamane formula calculations. The analysis method uses path analysis, apart from that, validity and reliability test are also carried out on the research instruments. Based on the research results of the independent variables, namely product quality and price, it shows that there is an influence on the dependent variable, namely purchasing decisions, of 83,2%. The influence of product quality variables on purchasing decisions is 26,5% and the influence of price on purchasing decisions is 56,7%